PENGARUH PROFITABILITAS, LIKUIDITAS, SOLVABILITAS, AKTIVITAS DAN UKURAN PERUSAHAAN TERHADAP PERTUMBUHAN LABA (Studi Empiris Pada Sektor Teknologi yang terdaftar di BEI Tahun 2019 - 2023) - Rahmadyah, Firlii; Indrabudiman, Amir (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This research was conducted with the aim of determining the influence of Profitability, Liquidity, Solvency, Activity and Company Size on Profit Growth in Technology Sector Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period. The sampling technique in this research used purposive sampling with a sample of 18 Technology Sectors listed on the Indonesian Stock Exchange that met the sample criteria. The data analysis used in this research is multiple linear regression analysis using statistical testing tools, namely SPSS version 22.0. Based on the research results, it can be concluded that profitability and solvency have a significant positive effect on profit growth, then company size has a significant negative effect on profit growth. Meanwhile, Liquidity and Activity have no effect on profit growth.